Neurogenesis-on-Chip: Electric field modulated transdifferentiation of human mesenchymal stem cell and mouse muscle precursor cell coculture. (January 2020) - Naskar, Sharmistha; Kumaran, Viswanathan; Markandeya, Yogananda S.; Mehta, Bhupesh; Basu, Bikramjit
Abstract: A number of bioengineering strategies, using biophysical stimulation, are being explored to guide the human mesenchymal stem cells (hMScs) into different lineages. In this context, we have limited understanding on the transdifferentiation of matured cells to another functional-cell type, when grown with stem cells, in a constrained cellular microenvironment under biophysical stimulation. While addressing such aspects, the present work reports the influence of the electric field (EF) stimulation on the phenotypic and functionality modulation of the coculture of murine myoblasts (C2C12) with hMScs [hMSc:C2C12=1:10] in a custom designed polymethylmethacrylate (PMMA) based microfluidic device with in-built metal electrodes. The quantitative and qualitative analysis of the immunofluorescence study confirms that the cocultured cells in the conditioned medium with astrocytic feed, exhibit differentiation towards neural-committed cells under biophysical stimulation in the range of the endogenous physiological electric field strength (8 ± 0.06 mV/mm). The control experiments using similar culture protocols revealed that while C2C12 monoculture exhibited myotube-like fused structures, the hMScs exhibited the neurosphere-like clusters with SOX2, nestin, βIII-tubulin expression. The electrophysiological study indicates the significant role of intercellular calcium signalling among the differentiated cells towards transdifferentiation. Furthermore, the depolarization induced calcium influx strongly supports neural-like behaviour for the electric field stimulated cells in coculture. The intriguing results are explained in terms of the paracrine signalling among the transdifferentiated cells in the electric field stimulated cellular microenvironment. In summary, the present study establishes the potential for neurogenesis on-chip for the coculture of hMSc and C2C12 cells under tailored electric field stimulation, in vitro .